The Effect of CEO Political Ideology on Firms' Implementation of ESOP and Work‐Family Benefits - Weng, David H.; Pichler, Shaun M. (Human Resource Management, 2026)
ABSTRACT Drawing on research on political ideology and the HRM literature, we postulate that the degree to which CEOs are politically liberal will affect firms' use of employee stock ownership plans (ESOP) and work‐family benefits in two distinct ways. First, political liberalism increases CEOs' motivation to practice egalitarianism (including more equal compensation). Second, liberalism steers CEOs to be open to practices that foster social changes. Hence, we contend that CEO political liberalism will increase the firm's likelihood of implementing ESOP and work‐family benefits. Further, we suggest that certain contingencies will moderate these associations. Results derived from a dataset of Fortune 500 firms based in the US from 2002 to 2018 ( n = 2,363) support our arguments. We measured ESOP by a binary variable indicating whether a firm implemented any stock ownership program in a year, while work‐family benefits was captured by a dummy suggesting whether a firm had a work‐life balance policy in a year. Our findings contribute to the literature on HRM practice implementation and political ideology.